Effectiveness of the interaction unit method in teaching addition and subtraction problem-solving skills to students with intellectual disability. - Karaaslan, Derya; Yıkmış, Ahmet (International Journal of Developmental Disabilities, 2026)
This study examines the effectiveness of the interaction unit method, which is presented virtually, in teaching addition and subtraction problem-solving skills to students with intellectual disability (ID). The research was conducted with three students (one girl and two boys) aged 15–16 years who were diagnosed with ID and were attending a special education vocational school in Istanbul. Multiple probe design with probe trials across the subjects was used. The dependent variables include the participants' level of solving addition and subtraction problems, and the independent variable is the teaching via the virtual interaction unit method (VIUM). We found that by using this method, students with ID could acquire the skills to solve addition and subtraction problems. Moreover, it was determined that the students continued to maintain these skills one and two weeks after the intervention and were able to generalize different environments, tools, and people. Considering the social validity of the research obtained from teachers' opinions, it was concluded that the opinions about the VIUM were positive.